O uso de cartilhas no processo de alfabetização : um estudo a partir de cadernos de planejamento de uma professora (1983-2000) - Vieira, Cícera Marcelina (2014)
This study aimed at identifying and mapping which books were used by a teacher in a rural school in the south of Rio Grande do Sul state, in Brazil, as a support to prepare lessons and teach early stages of reading and writing. The main corpus of analysis comprised twenty three plan books written from 1983 to 2000 by a teacher who was called A in this investigation. This period of time was chosen due to the fact that the sources were available and enabled a longitudinal analysis so that the books that were used to teach early stages of reading and writing throughout seventeen years could be traced back. The process of data analysis was carried out in two ways: i) it was based on notes - mentioning the book titles - written by the teacher in the plan books; and ii) it was based on the identification of activities called copying and reading. Results showed that the plan books under analysis represent the routine of both the class and the school. These plan books depicted a methodological sequence which tried to follow the gradual progression of learning difficulties, i. e., from the preparatory period to the vowels, vowel sequences and syllables. Activities described in the plan books focused on syllabication exercises, dictations and copies; it showed that the teacher’s practice was based on an associationist view of teaching/learning. The analysis of the books used in the early stages of reading and writing to help lesson preparation led to the mapping of a set of fourteen books. The titles of the most recent ones were: Pirulito, Alegria de Saber and É Hora de Aprender. The identification of this set led to the perception of which didactic books were used longer and whose principle was artificial reading, besides the gradual progression of learning difficulties, i. e., books in which lessons were organized from the simplest ones – canonic syllables – to the most complex ones – vowel sequences and digraphs. Regarding how these books were used, most activities were the literal transcription of the spelling books. Even when the teacher suggested some changes, the activities kept the “spelling book model”, thus, showing that, despite the debate about literacy triggered by Ferreiro & Teberosky’s studies of the Psychogenesis of the Written Language (1999) and by Soares’ concept of literacy (1999), the teacher’s practice kept ingrained in an associationist view of learning.